145 Nutritional Advances in Fetal and Neonatal Development: Methyl Donors. (30th November 2020) - Batistel, Fernanda
Abstract: The objective of this presentation is to discuss and review research on methyl donors in the developmental programming of dairy cattle. One-carbon metabolism is catalyzed by several enzymes in the presence of dietary micronutrients, including methionine, choline, betaine, and folate, and generates S-adenosylmethionine. S-adenosylmethionine is crucial for numerous cellular functions such as DNA and histone methylation as well as protein synthesis. Despite the biological role of S-adenosylmethionine, there is a limited understanding of the impact of dietary methyl donors' supply to pregnant dairy cows and neonatal calves. The majority of research related to methyl donors in fetal and neonatal development and physiology has been generated supplying methyl donors to dairy cows during the end of gestation. The results from recent studies are not conclusive, but overall they indicate that methyl donors supply during the end of pregnancy enhance calf performance and ameliorate immune response. A better understanding of the impact of methyl donors may offer new ways to augment development, performance and immune function of growing replacement heifers.